PENGARUH PERUBAHAN SUHU UDARA TERHADAP KONSUMSI LISTRIK PADA RUMAH TANGGA DAN BISNIS DI KOTA PEKANBARU - Hosi Riskiawan; Nobel Aqualdo; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Electrics energi have come to commodity requirement of primary in human life, because electrics represent form of energi very practical able to alter from one form to other form, for example altered into form of energi mechanic able to move machine at AC and fan. When air temperature or environmental temperature outside mount, usage of AC and fan very required to make cool temperature in room or house, because when of external air temperature mount, temperature in room also will be mount too, and electrics consumption also will be mount. This Skripsi explain how big influence of change of air temperature to electrics consumption at business and household in Pekanbaru and what factor is having a signifikan effect. For this research using data of sekunder, obtained fromPLN persero Pekanbaru institutions and Meteorology Station of Klimatologi and Geophysics ( BMKG) Sultan Syarif Kasim II Pekanbaru. Calculation process using statistical analysis, with doubled linear regression with stepwise method. The result for this research is primary factor influencing electrics consumption at business and household is the number of consumer. with coefficient of determinasi at household (R2 = 69,1%) rest 30,9% influenced by other factor, while coefficientof determinasi at business (R2 = 84,6%) rest 15,4% influenced by other factor. While change of temperature do not have an effect on signifikan to electrics consumption at business and household in Pekanbaru.Keywords : change of air temperature, electrics consumption, Household and Business